Method for preparing CT20 ultralow-temperature titanium alloy through laser directional energy deposition technology

Printing CT20 ultra-low temperature titanium alloy through laser directional energy deposition technology solves the problem of preparation of CT20 titanium alloy in the prior art, achieving high tensile performance and formation of mesh basket-like tissue, and improving the overall performance of the material.

CN119703113APending Publication Date: 2025-03-28CHANGAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734412.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult to effectively prepare CT20 ultra-low temperature titanium alloy in the prior art, and its application in laser energy deposition technology is relatively lacking, resulting in the quality and performance of molded parts not meeting actual needs.

Method used

Using laser directional energy deposition technology, four raw materials, Ti, Al, Mo and Zr, are mixed with specific weight ratios to form CT20 alloy powder, and are printed into CT20 ultra-low temperature titanium alloy through laser energy deposition technology.

Benefits of technology

The prepared CT20 titanium alloy has high tensile properties, and the tissue presents the iconic mesh basket-like tissue. As the number of printed layers increases and the power increases, the tissue refinement and tensile properties of the sample are further improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703113A_ABST
    Figure CN119703113A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy preparation, and relates to a method for preparing a CT20 ultralow-temperature titanium alloy by using a laser directional energy deposition technology. A method for preparing a CT20 ultralow-temperature titanium alloy through a laser directional energy deposition technology comprises the steps that four raw materials including Ti, Al, Mo and Zr are mixed according to the specific weight ratio to form CT20 alloy powder, and then the CT20 alloy powder is printed into the CT20 ultralow-temperature titanium alloy through the laser directional energy deposition technology. The prepared CT20 titanium alloy has high tensile property, the structure presents a symbolic basket-shaped structure, and the structure presents an obvious evolution rule along with the increase of the number of printing layers; along with the increase of power, crystal grains in a sample are finer, the basket shape of the structure is more obvious, and the tensile property at normal temperature is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy preparation, and relates to a method for preparing CT20 ultra-low temperature titanium alloy by utilizing laser directional energy deposition technology. Background Art

[0002] Laser directed energy deposition (DED) technology is a typical additive manufacturing technology. Its characteristics are that the laser forms a molten pool in the deposition area and moves at high speed, and the material is directly fed into the high-temperature melting zone in the form of powder or filaments, and deposited layer by layer after melting. In recent years, the aerospace field has widely used technologies such as laser directed energy deposition to repair damaged parts. The main advantage of this process is that it can repair and manufacture large parts and load-bearing structural parts, while also optimizing the structure and reducing the weight of parts. It breaks through the design limitations of traditional processing technology and can achieve composite processing, which has important economic and social benefits.

[0003] CT20 titanium alloy is a new type of low-temperature titanium alloy of Ti-Al-Zr-Mo series independently developed by my country. It has good low-temperature performance and processing performance, and has excellent strength, toughness and cold forming performance in low-temperature environment. It has been successfully used in various aerospace low-temperature structural parts such as low-temperature pipelines of aerospace equipment.

[0004] Currently, there is a lack of research on the preparation of CT20 titanium alloy materials using laser energy deposition technology. The production method of most CT20 titanium alloys is to melt the raw materials into ingots through two vacuum consumable arc melting processes. The quality and performance of the resulting molded parts cannot meet actual needs. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide a method for preparing CT20 ultra-low temperature titanium alloy using laser directed energy deposition technology.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing CT20 ultra-low temperature titanium alloy using laser directed energy deposition technology, wherein four raw materials, Ti, Al, Mo, and Zr, are mixed in a specific weight ratio to form CT20 alloy powder, and then the CT20 alloy powder is printed into CT20 ultra-low temperature titanium alloy using laser directed energy deposition technology.

[0008] Furthermore, the mass percentages of the four raw materials of Ti, Al, Mo and Zr are: Al powder: 2.5% to 3.5%; Zr powder: 2.5% to 3.5%; Mo powder: 0.5% to 1.5%; Ti powder: 91.5% to 94.5%.

[0009] Furthermore, the particle sizes of the Ti powder, Al powder, Mo powder and Zr powder are all 75 μm to 100 μm.

[0010] Furthermore, the four raw materials of Ti, Al, Mo and Zr are mixed by a ball mill, the rotation speed of the ball mill is 300r / min to 500r / min, and the ball milling time is 3h to 5h.

[0011] Furthermore, the equipment used in the laser energy deposition technology is a laser energy deposition equipment.

[0012] Furthermore, the laser power selected by the laser energy deposition equipment is 2500W-3000W, the scanning speed is 7mm / s-10mm / s, and the layer thickness is 350μm-500μm.

[0013] Furthermore, the laser energy deposition technology specifically includes the following steps: firstly, placing CT20 alloy powder into a laser powder feeder and selecting a specific substrate; then, evacuating the laser directed energy deposition equipment to a vacuum and filling it with an inert gas until the oxygen content drops to a specified value.

[0014] Furthermore, the substrate is a TC4 titanium alloy plate.

[0015] Furthermore, the inert gas is argon.

[0016] Compared with the prior art, the present invention has the following beneficial effects: the prepared CT20 titanium alloy has high tensile properties, and the structure presents a characteristic basket-shaped structure, and its structure shows an obvious evolution law as the number of printing layers increases; as the power increases, the grains in the sample become finer, the basket-shaped structure becomes more obvious, and the tensile properties at room temperature are also better. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0019] Figure 1 This is a specific flow chart for preparing CT20 titanium alloy in the present invention;

[0020] Figure 2 A specific flow chart of preparing micro-area tensile samples of CT20 titanium alloy in the present invention;

[0021] Figure 3 XRD diagrams of CT20 titanium alloys manufactured at different powers in Examples 1-3 of the present invention;

[0022] Figure 4 The stress-strain diagram of the CT20 titanium alloy manufactured at different powers at room temperature under transverse tension in Examples 1-3 of the present invention;

[0023] Figure 5 The stress-strain diagram of the longitudinal stretching of the CT20 titanium alloy manufactured at different powers at room temperature in Examples 1-3 of the present invention;

[0024] Figure 6 This is a SEM image of the transverse tensile fracture of the CT20 titanium alloy manufactured at 2500W power at room temperature in Example 1 of the present invention;

[0025] Figure 7 It is a partial enlarged view of the SEM image of the transverse tensile fracture of the CT20 titanium alloy manufactured at 2500W power at room temperature in Example 1 of the present invention;

[0026] Figure 8 This is a SEM image of the transverse tensile fracture of the CT20 titanium alloy manufactured at 2700W power at room temperature in Example 2 of the present invention;

[0027] Fig. 9 It is a partial enlarged view of the SEM image of the transverse tensile fracture of the CT20 titanium alloy manufactured at 2700W power at room temperature in Example 2 of the present invention;

[0028] Fig.10 This is a SEM image of the transverse tensile fracture of the CT20 titanium alloy manufactured at 3000W power at room temperature in Example 3 of the present invention;

[0029] Fig.11 It is a partial enlarged view of the SEM image of the transverse tensile fracture of the CT20 titanium alloy manufactured at 3000W power at room temperature in Example 3 of the present invention;

[0030] Fig.12 This is a SEM image of the longitudinal tensile fracture of the CT20 titanium alloy manufactured at 2500W power at room temperature in Example 1 of the present invention;

[0031] Fig.13 It is a partial enlarged view of the SEM image of the longitudinal tensile fracture of the CT20 titanium alloy manufactured at 2500W power at room temperature in Example 1 of the present invention;

[0032] Fig.14 This is a SEM image of the longitudinal tensile fracture of the CT20 titanium alloy manufactured at 2700W power at room temperature in Example 2 of the present invention;

[0033] Fig.15 It is a partial enlarged view of the SEM image of the longitudinal tensile fracture of the CT20 titanium alloy manufactured at 2700W power at room temperature in Example 2 of the present invention;

[0034] Fig.16 This is a SEM image of the longitudinal tensile fracture of the CT20 titanium alloy manufactured at 3000W power at room temperature in Example 3 of the present invention;

[0035] Fig.17 This is a partially enlarged SEM image of the longitudinal tensile fracture of the CT20 titanium alloy manufactured at 3000W power at room temperature in Example 3 of the present invention. DETAILED DESCRIPTION

[0036] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples of devices consistent with some aspects of the present invention as detailed in the appended claims.

[0037] like Figure 1 As shown, the present invention provides a method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology, wherein four raw materials of Ti, Al, Mo, and Zr are mixed in a specific weight ratio to form CT20 alloy powder, and then the CT20 alloy powder is printed into CT20 ultra-low temperature titanium alloy by laser energy deposition technology.

[0038] Furthermore, the mass percentages of the four raw materials Ti, Al, Mo and Zr are:

[0039] Al powder: 2.5% to 3.5%. The mass percentage of Al powder can be selected according to actual needs. The mass percentage of Al powder can be 2.5%, 3%, or 3.5%;

[0040] Zr powder: 2.5% to 3.5%. The mass percentage of Zr powder can be selected according to actual needs. The mass percentage of Zr powder is: 2.5%, 3%, and 3.5%;

[0041] Mo powder: 0.5% to 1.5%. The mass percentage of Mo powder can be selected according to actual needs. The mass percentage of Mo powder is: 0.5%, 1%, and 1.5%;

[0042] Ti powder: 91.5% to 94.5%. The mass percentage of Ti powder can be selected according to actual needs. The mass percentage of Ti powder is: 91.5%, 93%, and 94.5%.

[0043] Furthermore, the particle sizes of Ti powder, Al powder, Mo powder and Zr powder are all 75μm to 100μm. The particle sizes of Ti powder, Al powder, Mo powder and Zr powder can be selected according to actual needs. The particle sizes of Ti powder, Al powder, Mo powder and Zr powder can be 75μm, 80μm, 85μm, 90μm, 95μm and 100μm.

[0044] Furthermore, the four raw materials of Ti, Al, Mo and Zr are mixed by a ball mill, and the rotation speed of the ball mill is 300r / min~500r / min; the ball milling time is 3h~5h. The rotation speed and ball milling time of the ball mill can be selected according to actual needs. The rotation speed of the ball mill can be 300r / min, 350r / min, 400r / min, 450r / min, 500r / min, and the ball milling time can be 3h, 4h, 5h.

[0045] Furthermore, the equipment used in the laser energy deposition technology is a laser energy deposition equipment.

[0046] Furthermore, the laser power selected by the laser energy deposition equipment is 2500W~3000W, and the laser power can be selected according to actual needs, and the laser power can be: 2500W, 2600W, 2700W, 2800W, 2900W, 3000W; the scanning speed is 7mm / s~10mm / s, and the scanning speed can be selected according to actual needs, and the scanning speed is: 7mm / s, 8mm / s, 9mm / s, 10mm / s; the layer thickness is 350μm~500μm, and the layer thickness can be selected according to actual needs, and the layer thickness is 350μm, 400μm, 450μm, 500μm.

[0047] Furthermore, the laser energy deposition technology specifically includes the following steps: firstly, placing CT20 alloy powder into a laser powder feeder and selecting a specific substrate; then, evacuating the laser directed energy deposition equipment to a vacuum and filling it with an inert gas until the oxygen content drops to a specified value.

[0048] Furthermore, the substrate is a TC4 titanium alloy plate.

[0049] Furthermore, the inert gas is argon.

[0050] The present invention aims to explore the influence of different laser powers on the alloy formability and microstructure of traditional CT20 titanium alloy, reveal the organizational evolution behavior of CT20 titanium alloy during laser energy deposition, and explore its tensile properties at room temperature, so as to prepare an alloy with stable organization and good tensile properties.

[0051] The technical solution of the present invention is a method for laser energy deposition of CT20 ultra-low temperature titanium alloy under different laser powers. The micro-area tensile sample is prepared to better demonstrate the performance of CT20 ultra-low temperature titanium alloy, such as Figure 2 As shown, the preparation of micro-area tensile samples specifically includes the following steps:

[0052] Step 1: Prepare Ti powder, Al powder, Mo powder and Zr powder in a fixed weight ratio; at the same time, use a ball mill to mix the prepared powders at room temperature for 3 to 5 hours to fully mix the powders; finally, dry them in a vacuum drying oven at 350 to 400K for two hours to remove moisture. This process ensures the stability of the processing.

[0053] Step 2: Print the configured CT20 alloy powder at three different powers.

[0054] Step 3: Use the spark cutting method to cut the printed CT20 alloy into cubes of 10mm×20mm×15mm for microstructure characterization.

[0055] Step 4: Take out a sheet sample with a thickness of 0.4 mm from the printed alloy by using an electric spark cutting method, and take a micro-area tensile sample in the transverse and longitudinal directions of the sample sheet.

[0056] Steps 3 and 4 are performed in order to obtain samples for observing the performance of CT20.

[0057] The particle sizes of the Ti powder, Al powder, Mo powder and Zr powder in step 1 are all 75-100 μm.

[0058] The mass percentages of the four raw materials of Ti, Al, Mo and Zr are: Al powder: 2.5% to 3.5%; Zr powder: 2.5% to 3.5%; Mo powder: 0.5% to 1.5%; Ti powder: 91.5% to 94.5%.

[0059] Furthermore, the weighed Ti powder, Al powder, Mo powder and Zr powder are mixed in a ball mill, the ball-to-material mass ratio of the ball mill is 1:3, the rotation speed of the ball mill is 300 r / min-500 r / min, and the ball milling time is 3h-5h.

[0060] Furthermore, the laser power selected by the laser energy deposition equipment is 2500W-3000W, the scanning speed is 7mm / s-10mm / s, the layer thickness is 350μm-500μm, and the scanning speed is 7mm / s-10mm / s.

[0061] Furthermore, in the step 2, before starting printing, the CT20 alloy powder is placed in the laser powder feeder and a specific substrate is selected; then the laser directed energy deposition equipment is evacuated to a vacuum, and the protective gas valve is opened to inject protective gas (argon gas). When the gas pressure in the printing chamber reaches 8500Pa, the above operation is repeated twice, and the oxygen content drops to a certain value (about 400ppm); the substrate is a TC4 titanium alloy plate.

[0062] Furthermore, the formed CT20 titanium alloy sample was cut from the substrate, and the microstructure of the DED-formed CT20 titanium alloy was regulated through the feedback of SEM and XRD detection data.

[0063] Furthermore, the micro-area tensile sample in step 4 is a dog-bone type, with a length of 12 mm, a width of 4 mm on both sides, and a width of 0.8 mm in the middle.

[0064] Example 1

[0065] A CT20 ultra-low temperature titanium alloy prepared by laser energy deposition technology, wherein the preparation method specifically comprises the following steps:

[0066] (1) After 93% Ti powder, 3% Al powder, 1% Mo powder and 3% Zr powder are prepared, they are mixed in a ball mill for 5 hours. After the powders are fully mixed, they are placed in a vacuum drying oven at 393K for 2 hours to remove moisture.

[0067] (2) The prepared CT20 powder is placed in the laser powder feeder, and the TC4 titanium alloy plate is selected as the substrate. Before printing begins, the laser directed energy deposition equipment is evacuated to a vacuum, and the protective gas valve is opened to fill with inert gas (argon). When the gas pressure in the printing chamber reaches 8500Pa, the above operation is repeated twice, and the oxygen content drops to a certain value (about 400ppm).

[0068] (3) The selected laser printing power is 2500 W, the scanning speed is 8 mm / s, and the layer thickness is 350 μm, and CT20 titanium alloy formed by laser directed energy deposition is obtained.

[0069] Example 2

[0070] The difference between this embodiment and embodiment 1 is that:

[0071] (1) After 93% Ti powder, 3% Al powder, 1% Mo powder and 3% Zr powder are prepared, they are mixed in a ball mill for 5 hours. After the powders are fully mixed, they are placed in a vacuum drying oven at 393K for 2 hours to remove moisture.

[0072] (2) The prepared CT20 powder is placed in the laser powder feeder, and the TC4 titanium alloy plate is selected as the substrate. Before printing begins, the laser directed energy deposition equipment is evacuated to a vacuum, and the protective gas valve is opened to fill with inert gas (argon). When the gas pressure in the printing chamber reaches 8500Pa, the above operation is repeated twice, and the oxygen content drops to a certain value (about 400ppm).

[0073] (3) The selected laser printing power is 2700 W, the scanning speed is 8 mm / s, and the layer thickness is 350 μm, and CT20 titanium alloy formed by laser directed energy deposition is obtained.

[0074] Example 3

[0075] (1) After 93% Ti powder, 3% Al powder, 1% Mo powder and 3% Zr powder are prepared, they are mixed in a ball mill for 5 hours. After the powders are fully mixed, they are placed in a vacuum drying oven at 393K for 2 hours to remove moisture.

[0076] (2) The prepared CT20 powder is placed in the laser powder feeder, and the TC4 titanium alloy plate is selected as the substrate. Before printing begins, the laser directed energy deposition equipment is evacuated to a vacuum, and the protective gas valve is opened to fill with inert gas (argon). When the gas pressure in the printing chamber reaches 8500Pa, the above operation is repeated twice, and the oxygen content drops to a certain value (about 400ppm).

[0077] (3) The selected laser printing power is 3000 W, the scanning speed is 8 mm / s, and the layer thickness is 350 μm, and CT20 titanium alloy formed by laser directed energy deposition is obtained.

[0078] also, Figure 3 The XRD patterns of CT20 titanium alloys obtained at three powers of 2500W (Example 1), 2700W (Example 2) and 3000W (Example 3) are shown. It can be seen from the figure that the physical phase of the CT20 titanium alloy samples obtained at the three powers is mainly α-Ti, and the diffraction peak of the β phase is only the {100} peak and the diffraction peak is weak. As the power increases, the β phase diffraction peak gradually weakens, because a part of the β phase is broken under high power. As the power increases, the diffraction peak width expands, which indicates that grain refinement has occurred, which is more obvious at α{002} and α{101}.

[0079] Figure 4The stress-strain curves of CT20 titanium alloy transversely stretched at room temperature under three powers of 2500W (Example 1), 2700W (Example 2) and 3000W (Example 3) are shown. It can be seen from the figure that the samples prepared under the three powers broke after experiencing three stages of deformation, all showing continuous yielding. After the elastic deformation stage, the stress quickly increased to the peak value. There was no obvious yield platform in this process. After that, the CT20 titanium alloy sample was stretched and finally broke. At the same time, as the power increases, the yield point stress of the sample increases, and the elastic deformation stage is prolonged. This change trend shows that the transverse strength of the sample is positively correlated with the power. The higher the power, the higher the strength of the obtained sample.

[0080] Figure 5 The figure shows the stress-strain curves of the longitudinal tensile test of CT20 titanium alloy produced at three powers of 2500W, 2700W and 3000W at room temperature. It can be seen from the figure that the samples produced at the three powers experienced three stages of deformation before breaking, all showing continuous yielding. After the elastic deformation stage, the stress rapidly increased to the peak value, and the CT20 titanium alloy sample was stretched to the final fracture. As the power increases, the yield point stress of the sample increases, and the elastic deformation stage is prolonged. This trend shows that the strength of the sample in the longitudinal direction is positively correlated with the power. The higher the power, the higher the strength of the obtained sample. At the same time, the comparison Figure 4 and Figure 5 , it can be seen that the yield stress of the sample in the transverse direction is higher than that in the longitudinal direction, and the deformation stage is also longer, that is, the strength of the sample in the transverse direction is better than that in the longitudinal direction. This is because the longitudinal bottom and upper tissues are different during the laser energy deposition process, resulting in different strengths, and therefore it is easier to break.

[0081] Figure 6-Figure 11 Shown is 2500W( Figure 6-Figure 7 )、2700W( Figure 8-Figure 9 ) and 3000W( Figure 10-11 ) Fracture micromorphology of CT20 titanium alloys obtained under three powers after transverse stretching at room temperature observed under SEM. It can be seen from the figure that when the power is 2500W, the fracture of the material shows obvious intergranular fracture morphology and river-like patterns, which are typical brittle fracture characteristics. With the increase of power, when the power reaches 2700W, dimples can be seen on the fracture, showing the characteristics of ductile fracture. When the power reaches 3000W, the density of dimples on the fracture increases further, indicating that the toughness of the material is improved.

[0082] Figure 12-Figure 17 Shown is 2500W( Figure 12-13 )、2700W( Figure 14-15 ) and 3000W( Figure 16-17) Microscopic morphology of the fracture of CT20 titanium alloys made at three powers observed under SEM after longitudinal stretching at room temperature. It can be seen from the figure that when the power is 2500W, the fracture of the material shows the characteristics of transgranular cleavage, which is a brittle fracture. When the power is increased to 2700W, dimples appear on the fracture surface, showing a ductile fracture, and the toughness of the material is improved. When the power reaches 3000W, the density of the dimples is greater, the distribution is more uniform, and the toughness of the material is better. Comparison Figure 6 and Figure 7 It can be seen that under the same power, the dimples in the transverse direction are more evenly distributed and have a higher distribution density than those in the longitudinal direction after stretching, that is, the transverse toughness of the specimen is generally better than that in the longitudinal direction.

[0083] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.

[0084] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A method for preparing CT20 ultra-low temperature titanium alloy using laser directed energy deposition technology, characterized in that: The four raw materials of Ti, Al, Mo and Zr are mixed in a specific weight ratio to form CT20 alloy powder, and then the CT20 alloy powder is printed into CT20 ultra-low temperature titanium alloy through laser energy deposition technology.

2. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 1, characterized in that: The mass percentages of the four raw materials of Ti, Al, Mo and Zr are: Al powder: 2.5% to 3.5%; Zr powder: 2.5% to 3.5%; Mo powder: 0.5% to 1.5%; Ti powder: 91.5% to 94.5%.

3. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 1, characterized in that: The particle sizes of the Ti powder, Al powder, Mo powder and Zr powder are all 75 μm to 100 μm.

4. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 1, characterized in that: The four raw materials of Ti, Al, Mo and Zr are mixed by a ball mill, the rotation speed of the ball mill is 300 r / min to 500 r / min, and the ball milling time is 3 h to 5 h.

5. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 1, characterized in that: The equipment used in the laser energy deposition technology is a laser energy deposition equipment.

6. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 5, characterized in that: The laser power selected by the laser energy deposition equipment is 2500W-3000W, the scanning speed is 7mm / s-10mm / s, and the layer thickness is 350μm-500μm.

7. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 1, characterized in that: The laser energy deposition technology specifically includes the following steps: firstly, placing CT20 alloy powder into a laser powder feeder and selecting a specific substrate; then, evacuating the laser directed energy deposition equipment to a vacuum and filling it with an inert gas until the oxygen content drops to a specified value.

8. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 7, characterized in that: The substrate is a TC4 titanium alloy plate.

9. The method for preparing CT20 ultra-low temperature titanium alloy by using laser directed energy deposition technology according to claim 7, characterized in that: The inert gas is argon.